Literacy, Technology, and First Year Teachers: A Case Study - Emily Kearns Burke (Adult Education Research Conference, 2016)
This paper examines how first year teachers describe their preparation and use of technology to teach literacy. Findings indicate teachers feel confident but unsupported in their efforts.
Keywords: first year teachers; literacy; technology; teacher preparation programs